ANALYSIS OF MEDICAL RECORD MANAGEMENT IN THE SPECIAL LUNG HOSPITAL OF NORTH SUMATRA PROVINCE - Adinda, Faiza; Dany, Cut Nasywa Kesuma; Octavelia, Anggi Tri; Aldona, Cindy; Herawati, Putri; Khumaira, Luthfiah; Hasibuan, Rapotan; Hasibuan, Devi Chairani (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Medical records are a mandatory and important document in the management of hospital services. Based on the Minister of Health Regulation No. 24 of 2022, it is described that medical records consist of confidential patient identity data containing records of examination, treatment, medical actions, and other services that have been provided according to patient needs. Problems that occur in various departments include incomplete documents in the preparation, coding errors, and the wrong location of files in the filling selection. Inadequate storage space and sub-optimal filling systems also contribute to lost records and inefficient retrieval. This study aims to look at the medical record file management process at the UPTD Special Lung Hospital North Sumatra Province. This research uses descriptive qualitative research methods. The results showed that the UPTD Special Lung Hospital North Sumatra Province still uses hybrid medical record file, and electronic medical records at the coding and indexing stages, and the supporting factors of the medical record file management process include human resources, suitability of Standard Operational Procedures (SOP), facilities and infrastructure, and reporting carried out at the UPTD Special Lung Hospital North Sumatra Province still has obstacles in the medical record file management process, namely the assembling process, coding and indexing, and the medical record file storange process.